Differences in Father and Mother Involvement and the Factors that Influence It on Early Childhood Education - Neti Hernawati; Tin Herawati (SEA-CECCEP, 2020)
Parental involvement is an essential aspect of education, especially in Early Childhood Education (ECE). It will have a positive influence on children. However, several studies have shown that parents' involvement, both father and mother in education, is still superficial. This study aims to analyze: 1) The difference between father and mother regarding motivational belief, perception of invitation for involvement, perception of life context and involvement in education; 2) The influence of motivational belief, perception of request for involvement and perception of life context on the involvement of father and mother in children's education and 3) The factors have the most significant influence on the involvement of fathers and mothers on ECE. The research was conducted in two villages (Babakan Village and Dramaga Village) in Dramaga District, Bogor Regency. In this study, respondents were 101 mothers who have pre-school children participating in ECE in the two selected villages. Retrieval of data using interview techniques to respondents with a questionnaire tool. The research data analysis consisted of descriptive analysis, difference test, and multiple linear regression test. The results showed that parental involvement, motivational beliefs, requests for involvement from school-child teachers and life context differ significantly between mothers and fathers. Mothers have motivational beliefs, demand for school-teacher involvement and a higher life context than fathers have. The regression test results showed that fathers' involvement was positively influenced by children's age, per capita income, requests for involvement from children, requests for involvement from teachers, mothers' life context and father's life context. The factor contributing most to the father's involvement was the teacher's request for fathers' involvement. Meanwhile, maternal involvement was positively influenced by maternal age, father's motivational beliefs, maternal motivational beliefs, teacher involvement requests and mother's life context. The factor that gave the most significant contribution to maternal involvement was the father's low motivational belief.